Tracing the Intellectual History of the Knowledge Economy: An Analysis of OECD Publications within the International Political Economy Framework - V. I. Konnov; D. A. Talagaeva (Vestnik MGIMO-Universiteta, 2021)
The article delves into the genesis of the “knowledge economy” concept as a prime exemplification of the scholarly community's engagement in international politics, facilitated by organizations possessing both scientific and international prominence, such as the OECD. From its inception, the OECD has evolved into an intellectual hub, generating influential documents that exert a substantial impact on the national economic policies of a diverse array of countries, irrespective of their membership status within the organization. This study undertakes an assessment of the evolution of the “knowledge economy” concept within the OECD, employing a dual analytical framework that encompasses intellectual history and international political economy (IPE), with a predominant focus on the neo-Gramscian school of thought within the IPE paradigm.Our recourse to the neo-Gramscian branch of IPE serves the purpose of delineating the role played by the “knowledge economy” within the broader context of power dynamics and the competing interests of influential groups capable of wielding political and economic influence. Conversely, the intellectual history perspective is instrumental in elucidating the role of the “knowledge economy” in advancing the intellectual pursuits of the scholarly communities actively involved in its conceptual development. When viewed through this lens, the trajectory of the “knowledge economy” from its emergence within the OECD's discourse in the early 1990s to the contemporary era can be characterized as a self-contained cycle. Grounded in the tenets of the “new growth theory,” the “knowledge economy” proffered a perspective that envisaged sustained and intensive non-industrial growth predicated on the development of the electronic sector of the economy, inextricably linked to the academic realm. This nexus, in turn, served as the cornerstone of the “historical bloc” that crystallized as a consequence of the transition of OECD economies into post-industrial states, exercising considerable sway over the policy decisions of these nations. The “knowledge economy” concept, championed by the OECD, thus became emblematic of the vested interests of this historical bloc.The OECD's documentation in the 2000s, with its pronounced emphasis on the application of lessons gleaned from the electronic sector—demonstrating rapid transitions from research and development outcomes to commercially viable products—across diverse economic sectors, is indicative of the escalating influence wielded by this specific historical bloc. Nevertheless, the practical scope of this experiential transfer ultimately fell short of the expansive initial aspirations associated with the promotion of the “knowledge economy.” Consequently, the “knowledge economy” progressively receded from the purview of OECD documents in the 2010s, giving way to the emergence of the concept of the “digital economy.”